Secondary Stroke Prevention After Ischemic Stroke in Patients with Alzheimer’s Disease and Other Dementia Disorders - Zupanic, Eva (J Alzheimers Dis, 2020)
BACKGROUND: Recurrent ischemic stroke (IS) increases the risk of cognitive decline. To lower the risk of recurrent IS, secondary prevention is essential. OBJECTIVE: Our aim was to compare post-discharge secondary IS prevention and its maintenance up to 3 years after first IS in patients with and without Alzheimer’s disease and other dementia disorders. METHODS: Prospective open-cohort study 2007–2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Patients with dementia who experienced an IS (n = 1410; 332 [23.5%] with Alzheimer’s disease) were compared with matched non-dementia IS patients (n = 7150). We analyzed antiplatelet, anticoagulant, blood pressure lowering, and statin treatment as planned medication initiation at discharge and actual dispensation of medications at first, second, and third year post-stroke. RESULTS: At discharge, planned initiation of medication was higher in patients with dementia compared to non-dementia patients for antiplatelets (OR with 95% CI for fully adjusted models 1.23 [1.02–1.48]) and lower for blood pressure lowering medication (BPLM; 0.57 [0.49–0.67]), statins (0.57 [0.50–0.66]), and anticoagulants (in patients with atrial fibrillation – AF; 0.41 [0.32–0.53]). When analysis for antiplatelets was stratified according to the presence of AF, ORs for receiving antiplatelets remained significant only in the presence of AF (in the presence of AF 1.56 [1.21–2.01], in patients without AF 0.99 [0.75–1.33]). Similar trends were observed in 1st, 2nd, and 3rd year post-stroke. CONCLUSIONS: Dementia was a predictor of lower statin and BPLM use. Patients with dementia and AF were more likely to be prescribed antiplatelets and less likely to receive anticoagulants.